Dissociation in Desmond Stewarts Leopard in the Grass - Al-Muttalibi, Aziz Y. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
This paper intends toexplore dissociation as the literary idea structuring Stewarts novel.(1) The paper discusses this organizing idea on both structural and thematic levels. Some allusions to parallel instances in contemporary fiction are worked out to enhance the narrative conclusions of the study. In a strangely unique sense, Stewarts novel strikes a historical note in as much as the narrative events occur within the temporal span of the 1950s and a topographical reality in as much as the events and characters move on the soil of Cyropolisand Media names that respectively stand for Baghdad and Iraq. It may be noted that the imperial ideology is a sophisticated act. It has worked and flourished under the guises and assurances that the British arenot striving for so degrading thing as money.(2) Yet, this is one aspectof imperial reality. Another one is a sense of some painfully sought technical superiority that suffers when the intruders confront the alien. That some enlightened and non-prejudiced British individuals are disturbed by the devious workings of their own culture-patterns ultimately substantiates that dismaying destructiveness which damages the pretended uniformity of the group. But when the concept of cultural relativity is totally absent, we will have that dissociative act of racial conflict which is more damaging in its disruptive reality. The Kind of analysis being shown here requires a thoroughly different approach from that of the model adopted in Barthes’s "Textural Analysis" of Poe’s tale: ’’The Facts in the Case of M. Valdemar’’.(3)